Copanlisib synergizes with conventional and targeted agents including venetoclax in B- and T-cell lymphoma models - Tarantelli, Chiara (Blood Adv, 2020)
Copanlisib is a pan–class I phosphoinositide 3-kinase (PI3K) inhibitor with preferred activity toward PI3Kα and PI3Kδ. Despite the clear overall clinical benefit, the number of patients achieving complete remissions with the single agent is relatively low, a problem shared by the vast majority of targeted agents. Here, we searched for novel copanlisib-based combinations. Copanlisib was tested as a single agent, in combination with an additional 17 drugs in 26 cell lines derived from mantle cell lymphoma (MCL), marginal zone lymphoma (MZL), and T-cell lymphomas. In vivo experiments, transcriptome analyses, and immunoblotting experiments were also performed. Copanlisib as a single agent showed in vitro dose-dependent antitumor activity in the vast majority of the models. Combination screening identified several compounds that synergized with copanlisib. The strongest combination was with the B-cell lymphoma 2 (BCL2) inhibitor venetoclax. The benefit of the combination over single agents was also validated in an MZL xenograft model and in MCL primary cells, and was due to increased induction of apoptosis, an effect likely sustained by the reduction of the antiapoptotic proteins myeloid cell leukemia 1 (MCL1) and BCL-XL, observed in MCL and MZL cell lines, respectively. These data supported the rationale for the design of the Swiss Group for Clinical Cancer Research (SAKK) 66/18 phase 1 study currently exploring the combination of copanlisib and venetoclax in relapsed/refractory lymphomas.